TUNNEL DEHYDRATOR FOR LOW GLYCEMIC INDEX FLAKES: TECHNOLOGICAL FEATURES, ENERGY EFFICIENCY, AND PRODUCT QUALITY - Коваленко, Ігор (SWorldJournal, 2025)
The tunnel dehydrator represents a cutting-edge, energy-efficient solution for drying food products, particularly in the production of low-glycemic-index flakes. This innovation plays a crucial role in addressing the growing issues of diabetes and obesity